Human Leptospirosis in Malaysia: Reviewing the Challenges After 8 Decades (1925-2012). (May 2016) - Benacer, Douadi; Thong, Kwai Lin; Verasahib, Khebir Bin; Galloway, Renee L.; Hartskeerl, Rudy A.; Lewis, John W.; Mohd Zain, Siti Nursheena
The history and epidemiology of human leptospirosis in Malaysia from 1925 to 2012 are described. Previous studies have demonstrated that leptospirosis is an endemic disease in Malaysia occurring in both urban and rural locations. The number of cases has risen dramatically since the Ministry of Health Malaysia highlighted leptospirosis as a notifiable disease in 2010, with reported cases increasing from 248 cases in 2004 to 3604 in 2012. The incidence of infection among the population suggests that occupation, sex, age, ethnic background, water recreational activities, and sporting events are risk factors. A robust surveillance system is now in place to monitor temporal and spatial changes in the incidence and prevalence of infection and to identify risk areas and disease behavior. Despite extensive studies over the past decade, there is a still a need to describe local serovars in host carriers and the human population, with the view to develop an effective vaccine against leptospirosis.